Yield, and phenolic content of shiitake mushrooms cultivated on alternative substrates - Gaitán-Hernández, Rigoberto; Aquino-Bolaños, Elia Nora; Herrera, Maricela; Salmones, Dulce (Emirates Journal of Food and Agriculture, 2020)
The productivity of four strains of shiitake (Lentinula edodes) on diverse lignocellulosic by-products used as substrates were evaluated. The objective was to determine the correlation between the composition of the substrate with the productivity of carpophores and their polyphenol content. The fungi were produced on vineyard prunings (VP), sorghum stubble (SS), sugarcane bagasse (SB), and oak shavings (OS). The productivity was evaluated based on the biological efficiency (BE), production rate (PR), and yield (Y). To evaluate the effect on shiitake growth on the chemical composition of the substrates, the content of fiber [neutral detergent fiber (NDF), hemicellulose, cellulose, lignin] was determined before and after inoculation. Total phenolic compounds were quantified by spectrophotometry. The highest BE was observed for the IE-256 strain on SS (145.11%), and the highest PR for the IE-245 strain on SS (1.69%). The highest Y was observed for the IE-256 strain on SS (41.96%). The fiber results were significantly affected by growth period, strain, substrate, and the selected combinations of strains and substrates. The phenolic compound content of the carpophores was also significantly affected by substrate and strain; the lowest and highest values were obtained for the IE-256 strain on OS (1.5983 mg GAE*g-1) and SS (2.7197 mg GAE*g-1), respectively. On average, the highest carpophores production per substrate and strain corresponded to SS and IE-245, respectively. The carpophores of the IE-256 strain cultivated on SS could potentially present greater antioxidant activity because of their high polyphenol content.